ASAS LEGALITAS DALAM HUKUM PIDANA SEBAGAI SARANA PENANGGULANGAN PERKAWINAN ANAK - M. ZAINUDDIN; AHMAD ROSIDI (Universitas Mahasaraswati K. Mataram, 2024)
This study focuses on the principle of legality in criminal law as a means of dealing with child marriage. Child marriages, which continue to occur today, have become a social phenomenon in various regions, not only occurring among ordinary people, but also in Islamic boarding school environments. The approach method uses conceptual (conceptual approach) and statutory (statute approach). The legal materials used come from documented legal materials in the library. Analysis was carried out using descriptive analysis. This study resulted in the finding that child marriage is not a criminal act according to the principle of legality as regulated in Article 1 paragraph (1) of the Criminal Code (KUHP) because the prohibition on child marriage is clearly and firmly regulated in the jurisdiction of the Civil Law, especially Article 7 paragraph 1 of the Marriage Law. Moreover, this prohibition is not absolute because it can be excluded by the existence of Article 7 paragraph 2 which provides legal policy for court judges to grant requests for marriage dispensation requested by parents or guardians of children for very urgent and unavoidable reasons in order to protect the child. . On the other hand, the current criminal law policy as a means of overcoming child marriage does not contain terminology that clearly and firmly regulates the prohibition and sanctions for perpetrators of child marriage, but what is regulated is the prohibition of forced child marriage and making child marriage a means of exploiting children. Apart from that, the existence of Article 288 of the Criminal Code relating to the prohibition of sexual intercourse with children who are thought to be unfit for marriage has no force and at the same time there are indications of a conflict of norms with the existence of Article 7 paragraph 2 of the Marriage Law, in line with the positive legal theory which views the granting of marriage dispensations by The authorized institution can erase the perpetrator's mistakes to become a reason for forgiveness and justification in criminal law